Employment Protection and Venture Capital Investment: The Impact of Wrongful Discharge Laws - Wang, Wei; Yung, Chris (Management Science, 2025)
Wrongful discharge laws (WDLs) provide limits to the employment-at-will doctrine, and thus impair operating flexibility, increasing expected financial distress costs by making it costly to fire employees. This impairment is detrimental to start-ups, leading to a decline in venture capital (VC) investment. Using a difference-in-differences framework enabled by the staggered adoption of WDLs across the U.S. states, we show VC investment declines after a state adopts the good faith exception (the strongest form of WDL). This decline is most pronounced in sectors with high labor dependency. This paper was accepted by Victoria Ivashina, finance. Supplemental Material: The data files are available at https://doi.org/10.1287/mnsc.2023.01936 .